Effect of edoxaban on markers of coagulation in venous and shed blood compared with fondaparinux - Wolzt, Michael; Samama, Meyer M.; Kapiotis, Stylianos; Ogata, Koichiro; Mendell, Jeanne; Kunitada, Satoshi (Thrombosis and Haemostasis, 2011)
Edoxaban, an oral direct factor Xa (FXa) inhibitor, is in phase III clinical development for stroke prevention in atrial fibrillation and treatment of venous thromboembolism. The shed blood model allows for study of activated coagulation at a site of standardised tissue injury due to local release of tissue factor. The objective of this study was to evaluate the effect of three doses of edoxaban on markers of coagulation in shed and venous blood versus placebo and a standard prophylactic dose of fondaparinux. A total of 100 healthy male subjects were randomised to receive single doses of one of five treatments: subcutaneously administered fondaparinux 2.5 mg; orally administered edoxaban 30, 60, or 120 mg; or placebo. The primary objective was measurement of blood coagulation markers prothrombin fragment 1+2 (F1+2) and thrombinantithrombin (TAT) complex, and platelet activation marker β-thromboglobulin (β-TG), in venous and shed blood. Secondary objectives included pharmacokinetics, shed blood volume, and safety of edoxaban. Single doses of edoxaban caused rapid and significant decreases of F1+2, TAT, and β-TG in the shed blood model, indicating inhibition of thrombin generation and platelet activation. Inhibition was significantly less for fondaparinux versus edoxaban. Baseline-corrected F1+2, TAT, and β-TG values demonstrated sustained inhibition up to 24 hours for shed blood in the edoxaban groups but no significant inhibition in venous blood. Overall, edoxaban treatments were well tolerated. In conclusion, single oral doses of edoxaban 30, 60, or 120 mg caused rapid and sustained inhibition of coagulation up to 24 hours in the shed blood model.
Keywords: Coagulation markers; direct factor Xa inhibitor; edoxaban; fondaparinux; shed blood model